Perkembangan Bola Voli di Kota Palangka Raya - Eto Saputra; U.Z. Mikdar; Cukei (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2021)
This research was carried out with the aim of knowing the management of the Palangka Raya City Volleyball Sports Branch (PBVSI). This study uses a qualitative descriptive method with the research location at KONI Palangka Raya City PBVSI Sports Branch, Palangka Raya City. Sources of data are interviews and observations. From the results of research that has been done, the development of Volleyball in Palangka Raya City is 1) Short Medium Long Term Planning has a period of 5 years, 2 years, 1 year. 2) the condition of the Palangka Raya City PBVSI Organization which is coordinated is quite good. 3) The finances of the Palangka Raya PBVSI are good and tidy. 4) Human Resources Palangka Raya City PBVSI trainers who handle PBVSI Palangka Raya City already have a certificate and there is no certificate. PBVSI Palangka Raya athletes have good and quality playing skills. The PBVSI referee for Palangka Raya City already has a certificate. 6) The achievements of the PBVSI of Palangka Raya City which have been achieved so far are good and always experience development and progress.